The role of financial aid in college performance: the importance of class attendance - Gabaldón, Patricia; Sivatte, Isabel de (Universidad Politecnica de Valencia., 2023)
We use Social Identity Theory (SIT) and Tinto's (1975) theoretical framework on college dropout to argue how the provision of financial aid relates to undergraduate students' performance. Financial aid enables economically less favored students to pursue high quality university education achieving upward social mobility. We conduct this study using archival data of 4 cohorts of business administration undergraduate students of an international,elite university in Europe. We find that financial aid recipients obtain a higher first-year GPA than non-recipients. This positive relationship is partially mediated by class attendance. Financial aid recipients attend more classes,which also enhances their GPA. Moreover,unexpectedly,we find that the relationship between the amount of aid received and GPA is non-linear,and that merit-based aid and need-based aid increase students' GPA in a similar manner. © 2023 International Conference on Higher Education Advances. All rights reserved.
Keywords: Amount of financial aid; Class attendance; Management of education; Need- vs merit-aid; Student performance in higher education; 58 Pedagogía; ODS 4 - Educación de calidad; ODS 10 - Reducción de las desigualdades